Lcn2-derived Circular RNA (hsa_circ_0088732) Inhibits Cell Apoptosis and Promotes EMT in Glioma via the miR-661/RAB3D Axis - Jin, Tao; Liu, Mingfa; Liu, Yan; Li, Yuanzhi; Xu, Zhennan; He, Haoqi; Liu, Jie; Zhang, Yuxuan; Ke, Yiquan (Frontiers in Oncology, 2020)
Background: Glioma is the most common malignant tumor of the central nervous system, and often displays invasive growth. Recently, circular RNA (circRNA), which is a novel non-coding type of RNA, has been shown to play a vital role in glioma tumorigenesis. However, the functions and mechanism of lipocalin-2 (Lcn2)-derived circular RNA (hsa_circ_0088732) in glioma progression remain unclear. Methods: We evaluated hsa_circ_0088732 expression by fluorescence in situ hybridization (FISH), Sanger sequencing, and PCR assays. Cell apoptosis was evaluated by flow cytometry and Hoechst 33258 staining. Transwell migration and invasion assays were performed to measure cell metastasis and viability. In addition, the target miRNA of hsa_circ_0088732 and the target gene of miR-661 were predicted by a bioinformatics analysis, and the interactions were verified by dual-luciferase reporter assays. RAB3D expression was analyzed by an immunochemistry assay, and E-cadherin, N-cadherin, and vimentin protein expression were examined by western blot assays. A mouse xenograft model was developed and used to analyze the effects of hsa_circ_0088732 on glioma growth in vivo. Results: We verified that hsa_circ_0088732 is circular and highly expressed in glioma tissues. Knockdown of hsa_circ_0088732 induced glioma cell apoptosis and inhibited glioma cell migration, invasion, and epithelial-mesenchymal transition (EMT). We found that hsa_circ_0088732 negatively regulated miR-661 by targeting miR-661, and RAB3D was a target gene of miR-661. In addition, inhibition of miR-661 promoted glioma cell metastasis and suppressed cell apoptosis. Knockdown of RAB3D induced cell apoptosis and suppressed cell metastasis. Moreover, hsa_circ_0088732 accelerated glioma progression through its effects on the miR-661/RAB3D axis. Finally, results from a mouse xenograft model confirmed that knockdown of hsa_circ_0088732 induced miR-661 expression, resulting in suppression of RAB3D expression and inhibition of tumor growth in vivo. Conclusion: We demonstrated that hsa_circ_0088732 facilitated glioma progression by sponging miR-661 to increase RAB3D expression. This study provides a theoretical basis for understanding the development and occurrence of glioma, as well as for the development of targeted drugs.